Construction tools of the human being. The Medical report - Micucci, Federica E. (Medicina Historica, 2021)
In Italy, and in general in western society, there is an official certification for almost every event of our life. There is a specific document prepared by the national administrative machinery, regarding every event of our life such as birth, immigration, come of age, permission to drive, getting married, beginning and continuing the school career. The health state of the citizens is also included in this machinery. Apart from the health cards, concerning the health state and “connecting” them to a general practitioner, the citizens can have use of a series of health services provided by the national health institutions and therefore, can be in possession of one or more medical reports. With this work my aim is to contribute from an anthropologic perspective to the investigation on how human being-patient is created within the medical and administrative boundaries, in order to do so I will briefly analyse in anthropopoietic terms some aspects of Medical Report structuration history.